Reflection of High School and Physics Education Students' Views about Satellite Motion into Their Thought Experiments - (:unkn) unknown (HACETTEPE UNIV, 2014)
Thought experiments are executed in the mind without using equipment by operating an imaginary scenario with a specific purpose such as finding a solution, bringing an evidence, clarifying a concept, strengthening or refuting a theory. Although thought experiments have revolutionary impacts in the history of science, their role in science education has not been revealed yet. This research aims to present enlightening results about students' thought experimentation processes by investigating the effects of high school and university physics students' alternative views about satellite motion on this process. In this research, Thought Experiments Survey was applied to 50 tenth grade high school students (age 17) and 20 fourth year university students studying physics education. The data taken from a single question about satellite motion were taken within the scope of this study. Response categories were formed, and thought chains that shows the students' thought flows in each categories were drawn. Research results introduce the students' alternative views about satellite motion and show that these alternative views effect students' thought experimentation processes as deflectors in reaching the right conclusion. The results also illuminate the students' problem solving processes in the context of imaginary world.
Keywords: thought experiments; satellite motion; alternative views